The importance of modernizations in realization of sustainable development principles: A case study of the Heating Plant "Piast" in Bierun, Poland - Anna Szweda (Economic and Environmental Studies (E&ES), 2018)
The issue of environment protection has gained in importance recently in connection with progressive environmental decay, which is caused by a steady economic development and exploitative natural resource management. Energetics is one of the industries, which have a damaging influence on the environment, especially in the matter of air quality. Polish energetics is based on carbon-intensive fuels due to big coal reserves commanded by the country. Coal burning leads to air pollution emission of sulfur dioxide, carbon dioxide and particulate matter. Modernizations of power installations are one of the ways towards realization of sustainable development principles. The article is devoted to modernizations implemented in the Heating Plant 'Piast' based in Bierun, Poland. The investments embraced modernizations of the heating boilers and gas-cleaning plants, which constitute the IPPC installations. The author presents research results concerning the influence of conducted modernizations on the amounts of air pollution emissions.
Keywords: Q1; Q4; 330; sustainable development; environment protection; energetics; heating plant; modernizations of power installations; air pollution emission; air quality